Unrecognized dermatophyte infection in ichthyosis vulgaris - Grahovac, Maja (Array, 2009)
Summary: A case of unrecognized widespread dermatophyte infection associated with ichthyosis vulgaris and atopy is described. Our patient was a young woman in which the diagnosis of ichthyosis vulgaris and atopic dermatitis blocked the recognition of widespread dermatophyte infection for more than six months. The case showed some clinical peculiarities in terms of both extent of lesions and their clinical appearance